Electroconductive nanoscale topography for enhanced neuronal differentiation and electrophysiological maturation of human neural stem cells - Yang, Kisuk; Yu, Seung Jung; Lee, Jong Seung; Lee, Hak-Rae; Chang, Gyeong-Eon; Seo, Jungmok; Lee, Taeyoon; Cheong, Eunji; Im, Sung Gap; Cho, Seung-Woo (ROYAL SOC CHEMISTRY, 2017)
Biophysical cues, such as topography, and electrical cues can provide external stimulation for the promotion of stem cell neurogenesis. Here, we demonstrate an electroconductive surface nanotopography for enhancing neuronal differentiation and the functional maturation of human neural stem cells (hNSCs). The electroconductive nanopatterned substrates were prepared by depositing a thin layer of titanium (Ti) with nanograting topographies (150 to 300 nm groove/ridge, the thickness of the groove -150 mu m) onto polymer surfaces. The Ti-coated nanopatterned substrate (TNS) induced cellular alignment along the groove pattern via contact guidance and promoted focal adhesion and cytoskeletal reorganization, which ultimately led to enhanced neuronal differentiation and maturation of hNSCs as indicated by significantly elevated neurite extension and the upregulated expression of the neuronal markers Tuj1 and NeuN compared with the Ti-coated flat substrate (TFS) and the nanopatterned substrate (NS) without Ti coating. Mechanosensitive cellular events, such as beta 1-integrin binding/clustering and myosin-actin interaction, and the Rho-associated protein kinase (ROCK) and mitogen-activated protein kinase/extracellular signal regulated kinase (MEK-ERK) pathways, were found to be associated with enhanced focal adhesion and neuronal differentiation of hNSCs by the TNS. Among the neuronal subtypes, differentiation into dopa-minergic and glutamatergic neurons was promoted on the TNS. Importantly, the TNS increased the induction rate of neuron-like cells exhibiting electrophysiological properties from hNSCs. Finally, the application of pulsed electrical stimulation to the TNS further enhanced neuronal differentiation of hNSCs due probably to calcium channel activation, indicating a combined effect of topographical and electrical cues on stem cell neurogenesis, which postulates the novelty of our current study. The present work suggests that an electroconductive nanopatterned substrate can serve as an effective culture platform for deriving highly mature, functional neuronal lineage cells from stem cells.
Keywords: AUTISM SPECTRUM DISORDERS; FOCAL ADHESION MATURATION; ELECTRICAL-STIMULATION; NEURITE OUTGROWTH; MYOSIN-II; OSTEOGENIC DIFFERENTIATION; TYROSINE PHOSPHORYLATION; SUBSTRATE TOPOGRAPHY; ACTIN ORGANIZATION; TITANIUM SURFACES